The effect of lumbar multifidus muscle degeneration on upper lumbar disc herniation - Wang, Bingwen; Xu, Lifei; Teng, Peng; Nie, Lin; Yue, Hongwei (Frontiers in Surgery, 2024)
PurposeThis study aimed to investigate the effect of lumbar multifidus muscle (MF) degeneration on upper lumbar disc herniation (ULDH).MethodsThis study used 3.0T magnetic resonance imaging (MRI) T2 axial weighted images to retrospectively analyze 93 ULDH patients and 111 healthy participants. Sixty-five pairs of participants were included in this study using propensity score matching (PSM). Cross-sectional area, fat infiltration area, anteroposterior diameter (APD), lateral diameter (LD), cross-sectional area of the bilateral multifidus muscles at the corresponding level, intervertebral disc area at the corresponding section, and visual analog scale (VAS) score for low back pain (LBP). For inter-group comparisons, we used the t-test, analysis of variance (ANOVA), Mann–Whitney U test, Kruskal–Wallis test, chi-square test, or Fisher's exact test, according to the type of data. We used Pearson correlation analysis to study the correlation between the VAS score and related indicators, and established a predictive model for upper lumbar disc herniation using the receive operative characteristic (ROC) curve analysis method. Finally, univariate and multivariate logistic regression analyses were performed to establish a predictive model for the risk of high lumbar disc herniation.ResultsWe compared the fat areas at the lumbar vertebral levels L1/2, L2/3, and L3/4, as well as the left lateral diameter (LD) (MF), L1/2 left lumbar multifidus muscle index (LMFI), and L1/2 total fat infiltration cross-section area (TFCSA), and found significant differences between the case and control groups (P < 0.001). Furthermore, we observed a significant positive correlation (P < 0.05) between the VAS scores and multiple muscle indicators. Additionally, we developed ROC prediction models to assess the risk of lumbar intervertebral disc protrusion at the L1/2, L2/3, and L3/4 levels, with the results identifying L1/2 TFCSA, L2/3 TFCSA, and L3/4 relative psoas major muscle cross-section area (rPMCSA) as the most predictive indicators. Finally, univariate and multivariate logistic regression analyses showed that the L1/2 rPMCSA, L2/3 TFCSA were significantly associated with the risk of lumbar intervertebral disc protrusion in both models.ConclusionDegeneration of the MF is significantly correlated with the occurrence of ULDH, and the larger the area of fat infiltration in the MF, the more obvious the lower back pain in ULDH patients. In addition, TFCSA can serve as an indicator of the occurrence of ULDH.